Impacto da parametrização de microfísica de nuvens na simulação de um evento de precipitação extrema - Bem, Douglas Lima de (2023)
The present work aims to analyze the impact of different parameterizations of cloud microphysics together with the impact of topography on the performance of the regional model "Weather Research and Forecast" (WRF) in an extreme precipitation event which occurred in Petrópolis , in the state of Rio de Janeiro on February 15, 2022. Four simulations were performed using the microphysics parameterizations WRF Single-Moment 6-Class (WSM6) and WRF Double-Moment 6-Class (WD6M) and also varying The topographical parameters of the region are used, with the simulations starting at 00 UTC on 02/14/2022, prioritizing a spin-up day for the model, ending at 00 UTC on 16/ 02/2022 right after the end of the event. In the simulations, three nested domains were used, with the mother grid measuring 4.5km and the two nested grids measuring 1.5km and 500 m respectively, representing the second and third domains. As a secondary objective, the use of the variation of the vertical levels applied to the model was evaluated in order to observe variations in the presented results. In order to evaluate the data presented by the model, data from rainfall stations, located in the city of Petrópolis, from the National Center for Monitoring and Natural Disaster Alerts (CEMADEN) were used in order to analyze and quantify the model representation. In general, the simulations, observing the location of Petrópolis, showed an underestimation in relation to the accumulated precipitation, which may indicate a difficulty for the model to represent the precipitation data effectively and punctually. In comparison between the parameterizations, the WS6M was able to effectively present expressive accumulations throughout the event period, even displaced from the region, while the simulations that made use of WD6M presented accumulations below expectations. This situation can be explained by the sensitivity which the double moment parameterization has in relation to condensation nuclei (NdC’s). In the topographical scope, the refinement of the same did not show improvements in relation to the default topography of the model. When analyzing the variation of the vertical levels of the model, an improvement in the quantitative representation of the precipitation for the event itself was observed when the WS6M parameterization was used, while in the simulations that made use of the WD6M it was not observed impacts relevant to the event.